Corporate Short-Termism and Intertemporal Choice - Robert J. Rhee (Washington University Law Review, 2018)
This paper presents an intertemporal model of short-termism. Critics have portrayed short-termism in broad brushstrokes as the bane of corporate governance. But short-termism does not have a self-evident, efficiency-based normative value. A simple application of a well-accepted asset valuation theory shows that short-termism is not per se inefficient. If profitable enough, a short-term strategy would be better than a long-term strategy. This intuition is a mathematical and financial fact. The model presented here is tested in a case study of Air Products and Chemicals, Inc. v. Airgas, Inc., a prominent and legally significant Delaware hostile takeover battle. Short-termism was a key fact in the court’s legal analysis of the target’s poison pill defense. The case enables a counterfactual analysis of the financial returns based on the target’s intertemporal strategic choices and the time horizons of shareholders. The choice of a short-term strategy is contextual; the outcomes therefrom can result in random errors or rational outcomes. It can also result in a systemic social problem, but only when two levels of market inefficiency coexist: the corporate market is systemically biased in intertemporal decisions, and the capital market is inefficient in failing to incorporate this bias into stock prices. These conditions are special, occurring only infrequently. They are intrinsic qualities of a market bubble.
Keywords: Corporate law; Short-Termism; Intertemporal Choice; Air Products and Chemicals Inc. v. Airgas Inc.; asset valuation theory; corporate governance; market inefficiency; corporate market; capital market; Delaware Chancery Court; Counterfactual Analysis; Intertemporal Returns; Stock Price Analysis; short-term profit; long-term cost; business law